2020
DOI: 10.1002/aet2.10517
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency Practices of Residents in an Academic Emergency Department: A Mixed‐methods Study

Abstract: Background: Application for EM residency is becoming more competitive. Knowledge about geographic trends in matched residents may help programs streamline their recruitment process. Studies in other specialties have shown a high correlation between residency and medical school location.Objective: This study seeks to determine whether a correlation exists between the geographic location that an emergency medicine resident matched and their medical school location.Methods: We identified allopathic emergency medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Our findings build on existing literature that describes strategies for teaching ED flow, particularly for medical residents [ 8 14 ]. This literature emphasizes the importance of teaching management and leadership skills necessary for improving patient flow and efficiency through constructive feedback, leading by example, and providing opportunities for residents to discuss and practice patient flow management.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings build on existing literature that describes strategies for teaching ED flow, particularly for medical residents [ 8 14 ]. This literature emphasizes the importance of teaching management and leadership skills necessary for improving patient flow and efficiency through constructive feedback, leading by example, and providing opportunities for residents to discuss and practice patient flow management.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the gap in flow training for ED staff, limited academic literature outlines the specific concepts and strategies that should be employed in ED flow training. Existing literature has begun to address this gap by identifying and describing strategies for teaching ED flow, primarily to medical residents [ 9 14 ]. However, there is a need to identify a comprehensive list of topics and training methods for flow training for ED staff, including emergency physicians, nurse practitioners, nurses, and medical learners.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of publications have provided global recommendations for how residents can improve WFE, 3,[18][19][20][21] the specific approaches utilized by residency programs to teach these skills have not been described. Our study identified on-shift feedback as the most popular approach to teaching WFE, reported by 88% of re- While there is an overall paucity of resources on teaching efficiency, there are numerous possible ways this could be accomplished.…”
Section: Discussionmentioning
confidence: 99%